Effectiveness of HIV/AIDS Education Using Leaflets and Tiktok Videos for Adolescents in Panimbang District, Pandeglang Regency - E. Egriana Handayani; Siti Nur Ramdaniati (Malahayati Nursing Journal, 2026)
ABSTRACT HIV/AIDS among teenagers is a problem that is still quite high and has an impact on adolescent health. HIV/AIDS often occurs because sexual activity among teenagers is increasing due to knowledge about HIV/AIDS not being improved. Objective This research is to determine the effectiveness of counseling using leaflets and Tiktok video media for teenagers in Panimbang District, Pandeglang Regency in 2024. Method of this research is a quasi-experimental quantitative research with a two group pre-test and post-test design, data was collected using a pre-questionnaire.- test and post-test. The population of this study was 2425. The sample in this study was 378 respondents who were divided into 2 groups, 189 respondents as the leaflets outreach group and 189 respondents as the tiktok video outreach. Result: There was an increase in the average value of knowledge and attitudes between before and after HIV/AIDS education using leaflets and tiktok videos among teenagers in Panimbang District. Conclusion: HIV/AIDS education using TikTok video is more effective than leaflets. Keywords: Media, Leaflet, Knowledge, HIV/AIDS Education, Video Tiktok.